Integrated transcriptomic and metabolomic analysis of resistant and susceptible Nicotiana tabacum L. reveals the mechanisms of selenium-induced disease resistance to Phytophthora nicotianae - Zhang, Kai; Ma, Xiaohan; Li, Jiaying; Wang, Fazhan; Wang, Wenchao; Tian, Jiashu; Teng, Huanyu; Liu, Yingjie; Xu, Jiayang; Niu, Huiwei; Jia, Wei (Frontiers in Plant Science, 2025)
Tobacco black shank, a destructive soil-borne disease caused by Phytophthora nicotianae, severely impacts tobacco production. Selenium (Se) is a beneficial trace element known to enhance plant stress resistance. While previous studies indicated Se’s efficacy against black shank, its differential effects on tobacco varieties with contrasting innate resistance remain unexplored. Herein, we integrated physiological, transcriptomic, and metabolomic analyses to elucidate the mechanisms of Se-induced resistance in a resistant (K326) and a susceptible (Zhongyan 100) tobacco cultivar. Our results showed that foliar application of 8 mg/L Se significantly reduced disease incidence and enhanced antioxidant enzyme activities, membrane stability, and accumulation of protective compounds in both cultivars. Multi-omics analyses revealed that Se potently enhanced resistance in K326 by synergistically upregulating the phenylpropanoid biosynthesis pathway, promoting the synthesis of lignin precursors and phenolic acids, and maintaining purine metabolism to ensure energy supply. In contrast, the susceptible cultivar Zhongyan 100 showed limited metabolic capacity to translate Se-induced transcriptional changes into effective defence metabolite accumulation. These findings provide novel insights into the genotype-dependent mechanisms of Se-induced resistance and highlight the potential of precision Se application as a strategy to bolster defence in resistant cultivars against soil-borne diseases.